Treatment of a Developmental Groove and Supernumerary Root Using Guided Tissue Regeneration Technique - Zahra Alizadeh Tabari; Hamed Homayouni; Tahere Pourseyediyan; Armita Arvin; Derrick Eiland; Nima Moradi Majd (Hindawi Limited, 2016)
Introduction. The radicular groove is a developmental groove which is usually found on the palatal or lateral aspects of the maxillary incisor teeth. The present case is a maxillary lateral incisor with a small second root and a deep radicular groove. The developmental groove caused a combined periodontal-endodontic lesion. Methods. Case was managed using a combined treatment procedure involving nonsurgical root canal therapy and surgical periodontal treatment. After completion of root canal treatment, guided tissue regeneration (GTR) was carried out using decalcified freeze dried bone allograft (DFDBA) and a bioabsorbable collagenous membrane. Tooth also was splinted for two months. Results. After 12 months the tooth was asymptomatic. The periapical radiolucency disappeared and probing depth did not exceed 3 mm. Conclusion. Combined treatment procedure involving nonsurgical root canal therapy and surgical periodontal regenerative treatment can be a predictable technique in treating combined endodontic-periodontal lesions caused by radicular groove.